Nitrogen Use Efficiency of Irrigated Corn for Three Cropping Systems in Nebraska - Wortmann, C.S.; Tarkalson, D.D.; Shapiro, C.A.; Dobermann, A.R.; Ferguson, R.B.; Hergert, G.W.; Walters, D. (Wiley, 2011)
Nitrogen use efficiency (NUE) is of economic and environmental importance. Components of NUE were evaluated at in 32 irrigated corn (Zea mays L.) trials conducted across Nebraska with different N rates and where the previous crop was either corn (CC), drybean (Phaseolus vulgaris L.) (CD), or soybean [Glycine max (L.) Merr.] (CS). The mean grain yield with adequate nutrient availability was 14.7 Mg ha−1 When no N was applied, measured soil properties and irrigation water N accounted for <20% of the variation in plant nitrogen uptake (UN). Mean fertilizer N recovery in aboveground biomass was 74% at the lowest N rate compared with 40% at the highest N rate, a mean of 64% at the economically optimal nitrogen rate (EONR), and least with CD. Agronomic efficiency of fertilizer N averaged 29 kg grain kg−1 N at EONR and was also least with CD. Partial factor productivity of N averaged 100 kg grain kg−1 N at EONR, and was greater with CS compared with CC and CD. After harvest, residual soil nitrate nitrogen (RSN) in the 0‐ to 1.2‐m depth ranged from 21 to 121 kg ha−1 and increased with N rate. Mean RSN was 88, 59, and 59 kg ha−1 for CD, CC, and CS, respectively. High corn yields can be achieved with high NUE and low RSN by management to maximize profitability in consideration of yield potential, and by applying N at the right amount and time.